1981
DOI: 10.1007/bf00365694
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a DNA segment from rat liver mitochondria containing the genes for the cytochrome oxidase subunits I, II and III, ATPase subunit 6, and several tRNA genes

Abstract: The sequence of a 6.24 kb DNA segment of the mitochondrial genome from rat liver has been determined. It comprises several genes coding for mitochondrial protein subunits and five tRNA genes in the following order: cytochrome oxidase subunit I - tRNA (UCN) (Ser) -tRNA(Asp) - cytochrome oxidase subunit II - tRNALys -ATPase subunit - cytochrome oxidase subunit III -tRNA(Gly) - potential open reading frame - tRNA(Arg) -two potential open reading frames. The tRNA genes were detected by a computer search programme.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Sequencing and comparison to data in Genbank [28] revealed that they were homologous to the gene-encoding subunit II of rat mitochondrial cytochrome C oxidase [6]. One clone (El) of 606 bp was used in additional investigations, because it almost completely covered the mature COX II mRNA (aligned to bases 2141-2747), encoded by bases 2117-2800 of the mitochondrial H strand [7,29].…”
Section: Isolation Of Cox II Clonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing and comparison to data in Genbank [28] revealed that they were homologous to the gene-encoding subunit II of rat mitochondrial cytochrome C oxidase [6]. One clone (El) of 606 bp was used in additional investigations, because it almost completely covered the mature COX II mRNA (aligned to bases 2141-2747), encoded by bases 2117-2800 of the mitochondrial H strand [7,29].…”
Section: Isolation Of Cox II Clonesmentioning
confidence: 99%
“…Sequencing revealed that the cDNAs encoded all or part of the gene for cytochrome oxidase II (COX II) [6,7]. Cytochrome oxidase is the terminal enzyme in the electron transport chain located on the inner membrane of mitochondria, and it functions to generate adenosine triphosphate (ATP) required for cellular processes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Its sequence (784bp) was 99.8% identical to the sequence of the mitochondrial gene [13]. The cDNA for rat COX subunit VIc, spanning part of the coding and the 3 noncoding region, cloned into the PstI site of pBluescribe, was described previously [14].…”
Section: Cdna Probes Hybridization Conditions and Detectionmentioning
confidence: 99%
“…(ii) The other clone, pSG 16, contained sequences coding for subunit I of the mitochondrial cytochrome oxydase (18); this gene is located in the mitochondrial rather than the nuclear genome. An increase in its expression has been previously associated with colony senescence in the unicellular mold Podospora anserina (22,44).…”
Section: Resultsmentioning
confidence: 99%